Phenotypes of COPD patients with a smoking history in Central and Eastern Europe: the POPE Study. Issue 5 (11th May 2017) - Koblizek, Vladimir; Milenkovic, Branislava; Barczyk, Adam; Tkacova, Ruzena; Somfay, Attila; Zykov, Kirill; Tudoric, Neven; Kostov, Kosta; Zbozinkova, Zuzana; Svancara, Jan; Sorli, Jurij; Krams, Alvils; et al.
Chronic obstructive pulmonary disease (COPD) represents a major health problem in Central and Eastern European (CEE) countries; however, there are no data regarding clinical phenotypes of these patients in this region. Participation in the Phenotypes of COPD in Central and Eastern Europe (POPE) study was offered to stable patients with COPD in a real-life setting. The primary aim of this study was to assess the prevalence of phenotypes according to predefined criteria. Secondary aims included analysis of differences in symptom load, comorbidities and pharmacological treatment. 3362 patients with COPD were recruited in 10 CEE countries. 63% of the population were nonexacerbators, 20.4% frequent exacerbators with chronic bronchitis, 9.5% frequent exacerbators without chronic bronchitis and 6.9% were classified as asthma–COPD overlap. Differences in the distribution of phenotypes between countries were observed, with the highest heterogeneity observed in the nonexacerbator cohort and the lowest heterogeneity observed in the asthma–COPD cohort. There were statistically significant differences in symptom load, lung function, comorbidities and treatment between these phenotypes. The majority of patients with stable COPD in CEE are nonexacerbators; however, there are distinct differences in surrogates of disease severity and therapy between predefined COPD phenotypes. Distinct phenotypes of COPD in Central and Eastern Europe have differences in symptoms, comorbidities and treatment http://ow.ly/oMZI307ndr5